AVALIAÇÃO DO DESEMPENHO COGNITIVO EM IDOSOS COM HIPERTENSÃO ARTERIAL NO MUNICÍPIO DE TRÊS LAGOAS/MS: ASSOCIAÇÃO COM VARIÁVEIS SOCIODEMOGRÁFICAS E DE SAÚDE. - CAROLINE BORGES CORREA (2023)
The prevalence of Arterial Hypertension (AH) in the older adult population is high, reaching 65% in Brazil. Since the incidence rates are also high, AH is considered the leading risk factor for other cardiovascular, cerebrovascular, and renal morbidities. Studies indicate that the brain of hypertensive elderly people, in the long term, presents significant vascular alterations, such as microvascular rarefaction, an increase in ischemic regions, and hypoperfusion of the white matter, which culminate in cognitive impairment. The present study aimed to evaluate the prevalence of cognitive deficit in older adult people with AH in Três Lagoas/MS, monitored in Primary Health Care, and to correlate the presence of cognitive deficit with sociodemographic and health variables. In this cross-sectional epidemiological study, with primary data, interviews were conducted with 376 older adult people with AH being followed up at Primary Health Care in the city of Três Lagoas/MS. The International Physical Activity Questionnaire (IPAQ), the Mini Mental State Examination (MMSE), and a pre-elaborated questionnaire with sociodemographic and health data were used. Of the total number of hypertensive older adult individuals assessed, 41.8% (95%CI = 36.9 – 46.8) presented cognitive impairment-associated scores. In applying the IPAQ, 54.5% of older adults were classified as physically inactive. When comparing the groups with and without indications of cognitive impairment, a significant difference was observed for the variables age (p=0.001), work (p=0.015), time since diagnosis (p=0.006), who separates the medication (p=0.001), and physical activity (p=0.017). In the final regression model, we observed significant differences between the groups for the variables age (odds ratio=1.03), time of diagnosis (odds ratio=1.74) and who separates the medication from the older adult (odds ratio=2.42). We can conclude that hypertensive older adult people in Três Lagoas have significant levels of cognitive impairment, which seems to be associated with older age, longer time since diagnosis, and who separates the medication from the older adult. Keywords: Hypertension; aging; cognition; geriatric nursing.